COMPARATIVE ANALYSIS OF MORPHOFUNCTIONAL INDICES OF THE THYROID GLAND IN INDIVIDUALS WHO HAVE HAD CORONAVIRUS - Hilola Sh. Yakhyoeva; Aziza B. Nazarova (Central Asian Journal of Medicine, 2024)
A number of targeted scientific studies are being conducted around the world to study the impact of coronavirus infection on the thyroid gland. World scientists claim that there are ACE2 receptors in the tissues of the hypothalamus and pituitary gland, and it has been established that these glands are damaged by SARS-CoV-2 directly or as a result of the immune process. However, at present, the pathophysiological features and clinical significance of the impact of SARS-CoV-2 on the organs of the endocrine system, as well as the impact of concomitant endocrine dysfunction on the prognosis of patients infected with coronavirus, have not been fully studied and are insufficiently covered in the literature. Given that coronavirus infection can lead to autoimmune thyroiditis or subacute thyroiditis, it is especially important to improve early diagnosis and treatment measures, as well as early assessment of the possibility of disability.